PLANNING SURFACE LEVEL HELIPORT AT LABUAN BAJO KOMODO AIRPORT - Putra, Panca Andi Pradana; Fatimah, Siti; Rozi, Fahrur (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2024)
Komodo Airport has a runway with dimensions of 2,650 m x 45 m and a PCN value of 55 F/C/X/T. The airport also has two aprons, apron A measuring 220 x 100 m with an asphalt surface, and apron B measuring 91 x 100 m with a rigid surface. As Komodo Airport is strategic and growing rapidly, a plan for the construction of a Surface Level Heliport has been developed using Annual Departure data and determination of helicopter plans. The development is planned with dimensions of 32 x 32 m for the largest helicopter, SUPER PUMA, with a budget of Rp 1,475,170,512. (one billion four hundred seventy-five million one hundred seventy thousand five hundred twelve rupiah).